PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA NON FISIK TERHADAP KEPUASAN KERJA KARYAWAN PADA RUMAH SAKIT KATOLIK SANTO ANTONIUS KARANG UJUNG AMPENAN - EGENIUS SIBA (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
This research is aimed at determining the partially and simultaneously significant effect and dominant effect of variables of leadership style, organisation culture, and non-physical work environment on the work satisfaction of employees of Santo Antonius Catholic Hospital Karang Ujung Ampenan. This research is explanatory study with 89 samples selected  from 115 collected through questionnaiers  and analysed with multiple linear regression, f-test, t-test  and  R2 test. The research showed  that there is partially  and simultaneously significant  effect of leadership style, organisational culture and non-physical  work environment on the work satisfaction of Santo Antonius Catholic Hospital Karang Ujung Ampenan, and non physical work environment has the most dominant effect on the work satisfaction of Santo Antonius Catholic Hospital Karang Ujung Ampenan. Keywords :     leadership style, organisation culture, non-physical work environment, work satisfaction.